ESCRT‐dependent vacuolar sorting and degradation of the auxin biosynthetic enzyme YUC1 flavin monooxygenase. Issue 9 (19th March 2019) - Ge, Chennan; Gao, Caiji; Chen, Qingguo; Jiang, Liwen; Zhao, Yunde
Summary: YUC flavin monooxygenases catalyze the rate‐limiting step of auxin biosynthesis. Here we report the vacuolar targeting and degradation of GFP‐YUC1. GFP‐YUC1 fusion expressed in Arabidopsis protoplasts or transgenic plants was primarily localized in vacuoles. Surprisingly, we established that GFP‐YUC1, a soluble protein, was sorted to vacuoles through the ESCRT pathway, which has long been recognized for sorting and targeting integral membrane proteins. We further show that GFP‐YUC1 was ubiquitinated and in this form GFP‐YUC1 was targeted for degradation, a process that was also stimulated by elevated auxin levels. Our findings revealed a molecular mechanism of GFP‐YUC1 degradation and demonstrate that the ESCRT pathway can recognize both soluble and integral membrane proteins as cargoes. Abstract : ESCRT complex is well known for its role in sorting and targeting membrane proteins for degradation. This study shows that the key auxin biosynthesis enzyme YUC1, a soluble and cytosolic protein, also adopts the ESCRT‐dependent vacuole sorting and degradation pathway.